Enhancing healthcare operations: a systematic literature review on approaches for hospital facility layout planning - dos Santos, Vinícius Carrijo [UNESP]; Siqueira, Regiane Máximo [UNESP]; Godinho-Filho, Moacir (Emerald, 2025)
Purpose: The appropriate physical layout of hospital services can help resolve management problems by streamlining the work of medical teams, improving the flow of patients between specific areas and the medical support environment. Nevertheless, the academic literature lacks structured research into how the physical layout of hospitals might be improved. Our study aims to fill this research gap, providing information for researchers and professionals who intend to guide the hospital facility layout planning (HFLP) from the steps and prescribed approaches found in the literature. Design/methodology/approach: This study analyzes the current literature status and concerning approaches that support HFLP and identifies their strengths and weaknesses. The literature was classified using the following criteria: approaches for layout generation, approaches for layout evaluation and healthcare facility layout outcomes. Findings: The hospital facility layout outcomes achieved for each phase served as a basis for identifying a list of strengths and weaknesses for the hospital layout facility generation and evaluation approaches. Readers can refer to this paper to identify the approach that best fits the desired goal and the HFLP step. Practical implications: This is a contribution to current studies into HFLP, and it provides guidelines for selecting the approach to be utilized based on the desired outcome. Originality/value: The paper describes how to conduct an HFLP and lists the strengths and weaknesses of each approach. The research may be used as a strategy for determining which tool is most suited based on the practitioner's target purpose.
Keywords: Flow; Healthcare facility layout outcomes; HFLP; Hospital facility layout planning; Layout evaluation; Layout generation; Strengths; Weaknesses